Clinical significance of postpancreatectomy acute pancreatitis defined by the International Study Group for Pancreatic Surgery. Issue 6 (1st June 2022) - Ikenaga, Naoki; Nakata, Kohei; Fujita, Nobuhiro; Abe, Toshiya; Ideno, Noboru; Ishigami, Kousei; Nakamura, Masafumi
Abstract: Aim: The International Study Group for Pancreatic Surgery (ISGPS) developed a structured definition of postpancreatectomy acute pancreatitis (PPAP) in 2021. This study aimed to evaluate the clinical significance of PPAP as defined by the ISGPS criteria. Methods: We evaluated the medical records and postoperative computed tomography (CT) findings of 247 patients who underwent pancreaticoduodenectomy. Postoperative hyperamylasemia (POH) was defined as an elevation in serum amylase levels over the upper baseline limit (≥133 U/L) on postoperative days 1 and 3. PPAP was defined as acute pancreatitis satisfying the following three requirements: POH, clinically relevant deterioration, and radiologic features consistent with acute pancreatitis. Results: Postoperative hyperamylasemia and PPAP were prevalent in 9.7% (24/247) and 3.6% (9/247) of the patients, respectively. PPAP grade B occurred in eight patients, seven of whom experienced Clavien–Dindo grade IIIA complications, including postoperative pancreatic fistula (POPF) and extended periods of postoperative hospitalization. PPAP grade C occurred in one patient, who died from the exacerbation of underlying interstitial pneumonia following the POPF occurrence. Acute pancreatitis determined by CT was observed in 15.3% (38/247) of the patients who underwent pancreaticoduodenectomy and was strongly associated with severe morbidity ( P < .0001) and longer postoperative hospitalization ( P < .0001). POH preceded acute pancreatitis on CT in only 23.7% (9/38) of those cases, resulting in a low incidence rate of PPAP. Conclusion: Post‐pancreatectomy acute pancreatitis is a major postoperative complication of pancreatic resection; however, based on the current ISGPS criteria, its prevalence is low. Defining PPAP promotes universal evaluation and understanding of this new concept. Abstract : The International Study Group for Pancreatic Surgery developed a structured definition of post‐pancreatectomy acute pancreatitis (PPAP) in 2021. We demonstrated the prevalence and clinical significance of PPAP by evaluating medical records and postoperative CT findings of 247 patients who underwent pancreaticoduodenectomy.